The Discovery and Characterization of Minimoon 2024 PT5 - Bryce T. Bolin; Larry Denneau; Laura-May Abron; Robert Jedicke; Kristin Chiboucas; Carl Ingebretsen; Brian C. Lemaux (The Astrophysical Journal Letters)
Minimoons are asteroids that become temporarily captured by the Earth–Moon system. We present the discovery of 2024 PT _5 , a minimoon discovered by the Asteroid Terrestrial-impact Last Alert System Sutherland telescope on 2024 August 7. The minimoon with heliocentric semimajor axis, a  ~ 1.01 au, and perihelion, q  ~ 0.99 au, became captured by the Earth–Moon system on 2024 September 29 and left on 2024 November 25 UTC. Visible g , r , i , and Z spectrophotometry was obtained using Gemini North/Gemini Multi-Object Spectrograph on 2024 September 27. The color indices are g − r = 0.58 ± 0.04, r − i = 0.29 ± 0.04, and i​​​​​​ ​ − Z = −0.27 ± 0.06, and the spectrum best matches lunar rock samples followed by S-complex asteroids. Assuming an albedo of 0.21 and using our measured absolute magnitude of 28.64 ± 0.04, 2024 PT _5 has a diameter of 5.4 ± 1.2 m. We also detect variations in the lightcurve of 2024 PT _5 with a 0.28 ± 0.07 mag amplitude and a double-peaked period of ~2600 ± 500 s. We improve the orbital solution of 2024 PT _5 with our astrometry and estimate the effect of radiation pressure on its deriving an area-to-mass ratio of 7.02 ± 2.05 × 10 ^−5 m ^2 kg ^−1 , implying a density of  ~3.9 ± 2.1 g cm ^−3 , compatible with having a rocky composition. If we assume 2024 PT _5 is from the near-Earth object (NEO) population, its most likely sources are resonances in the inner Main Belt when we compare its orbit with the NEO population model though this does not exclude a lunar origin.